The psychological effects of isolation exhaustion caused by home quarantine due to the Coronavirus (COVID-19) pandemic on the citizens in the Sultanate of Oman - Al-Busafi, Salim Rashid (Journal of Educational and Psychological Sciences, 2021)
The study aimed to identify the psychological effects of isolation exhaustion that caused by home quarantine due to the Coronavirus (COVID-19) pandemic among citizens in the Sultanate of Oman, and the research sample consisted of (1048) citizens of the Sultanate of Oman, ranging in age from (13 years to 61 years and over). The study tools included the isolation exhaustion scale, its psychometric properties were verified before its application, and the data were analyzed using Programme (SPSS). The results of the research showed that there are statistically significant differences at the level of significance (α= 0.05) between the computational circles of isolation exhaustion that caused by home quarantine due to the Coronavirus pandemic (COVID-19) among the citizens in the Sultanate of Oman attributed to marital status and age variables, and the results of the study also showed that there are no statistically significant differences at the significance level (0.05 = α) between the computational circles of isolation exhaustion that caused by home quarantine due to the Coronavirus pandemic (COVID-19) among the citizens in the Sultanate of Oman attributed to gender and housing variables. According to the research results, the researcher recommended several recommendations, including: The need to pay attention to the mental health of individuals under (21) years of age, through effective awareness-raising that focuses on the developmental characteristics of the age stage; and provide the psychological and social support to individuals, especially those under (21) years old.